- #1

- 281

- 0

## Main Question or Discussion Point

Hi,

in the method -Theory of Fixed Point Iteration of x = g(x)

If the function g(x) has several roots, why sometimes we need to change the form of g(x) to find the other roots?

For example we can have x

one form can be x= -x

or

another form can be

x=sqrt(-x

those two forms converge into diffrent values.WHY?

Thank you

Brad

in the method -Theory of Fixed Point Iteration of x = g(x)

If the function g(x) has several roots, why sometimes we need to change the form of g(x) to find the other roots?

For example we can have x

^{3}+3x^{2}+x+4,one form can be x= -x

^{3}-3x^{2}-4or

another form can be

x=sqrt(-x

^{3}-3x^{2}-4) / sqrt (3)those two forms converge into diffrent values.WHY?

Thank you

Brad